Characterization and Designing Integral Sliding Mode Controller for 2-Link Robot System with Coulomb Friction - Tu'ma, Dena Hameed; Hammoudi, Ahmed K. (Al-Nahrain Journal for Engineering Sciences, 2020)
The indemnification of uncertainty and disturbance which is added to non-linear systems by an Integral Sliding Mode Controller (ISMC) design. the key target of this paper is designing a sturdy controller to observe the performance of a 2-link robot. The nonlinearity in mechanical systems is a shared issue that the researchers are facing in formulating control systems for it. The best solution to this problem is a design Sliding Mode Controller (SMC) for controlling a nonlinear system. In the current paper, 2-link robot is studied which suffering from disturbances and parameter uncertainty and coulomb friction as additional to friction inertia of the system for each link. firstly, Classical Sliding Mode Controller (CSMC) is designed and then Integral Sliding Mode Controller (ISMC). As known, CSMC includes two phases: reaching phase and sliding phase. SMC is suffering from the known phenomenon as "chattering" which is supposed as a critical case and unsuitable characteristic. chattering is described as a curvy movement span the switching surface. In the current study, the chattering is attenuated by employing a saturation function alternative of a sign function. Although SMC can be considered as a good way of controlling nonlinear systems. Where it continues to suffer from the long settling time as undesired features. ISMC is a good method can be employed for reducing the settling time and controlling a nonlinear system. ISMC is easy, robust execution and supposes as an active and strong technique. The most significant advantage in ISMC designing, the reaching phase is canceled that considered a major part of designing classical SMC. The 2 link Robot system was used for proving the performance of CSMC and ISMC algorithms. The outcomes received from the simulations utilizing the ISMC and CSMC which fulfilled asymptotic stability for the system. In comparative between CSMC and ISMC. ISMC is better than CSMC in the good performance of tracking the desired position with less time. Finally, MATLAB2019a software package has relied upon this work.